Elementary students’ creative thinking skills in science in the Maluku Islands, Indonesia - Leasa, Marleny; Batlolona, John Rafafy; Talakua, Melvie (Creativity Studies, 2021)
Learning that encourages the development of students’ creative thinking needs to be maximized since the level of primary education, including in the disadvantaged, outermost, and frontier regions that is referred to 3T areas (terdepan, terluar, tertinggal) in Indonesia is still categorized as underdeveloped that requires special attention. The main objective of this research was to diagnose students’ creative thinking skills for four components including fluency, flexibility, originality, and elaboration on students in the islands. The study was conducted on 161 students sitting in fourth grade from 6 elementary schools. The unique thing why this research was conducted because the research location was one of the Maluku Islands, which has abundant sea, air and land in terms of natural resources and is one of the areas that borders directly with Australia, so it can be predicted students’ creative thinking skills will be good. However, the analysis results report that students’ creative thinking skills were still very low and thus require comprehensive learning improvement to improve students’ creative thinking skills. It was hoped that good creative thinking skills of students will support better regional development in the future.